Surgical Aspects of Ovarian Tissue Removal and Ovarian Tissue Transplantation for Fertility Preservation - Beckmann, M. W.; Dittrich, R.; Findeklee, S.; Lotz, L. (Geburtshilfe und Frauenheilkunde, 2016)
Introduction: The removal of ovarian tissue prior to starting oncologic treatment and the subsequent transplantation of this tissue after completing therapy have become increasingly important surgical fertility-preserving techniques. The aim of this review was to investigate the different surgical techniques used for this method reported in the literature to date and to discuss the advantages and disadvantages of the respective techniques. Review: A search was done in MEDLINE using a defined algorithm to find studies published between January 2004 and December 2015. All study designs were included in our review if they contained statements on the surgical technique used. We found 16 publications (8 retrospective cohort studies, 6 case reports and 2 systematic reviews) with a total of 1898 female patients which reported on the surgical technique used for ovarian biopsy and 15 publications (7 retrospective cohort studies, 6 case reports and 2 systematic reviews) with a total of 455 women which mentioned the surgical technique used for ovarian transplantation. Different surgical techniques can be used both for ovarian biopsy and for the transplantation of ovarian tissue. A number of different surgical routes have been used, and the amount of tissue extracted, the instruments used, the treatment of the ovary, the transplantation site, the blood supply to the transplanted ovarian tissue and the procedure used for simultaneous surgical interventions vary. Conclusion: In future, one of the tasks will be to establish a standard surgical method for ovarian extraction and transplantation which will have a low rate of complications and a high pregnancy and birth rate while ensuring that the transplanted tissue is fully functional.
Keywords: surgical techniques; ovarian tissue; fertility protection in cancer; fertility preserving techniques; oncofertility